GREEN ECONOMY: A PATHWAY TO SUSTAINABLE DEVELOPMENT - Dr Ishfaq Ahmad Bhat; Aamer Nabi Ganaie; Irshad Ahmad Reshi (RADJA PUBLIKA, 2023)
ABSTRACT The notion of a green economy has gained popularity as an innovative strategy to attaining sustainable growth while limiting the negative environmental repercussions of human activities. This study seeks to give an in-depth examination of the green economy, including its definition, principles, advantages, obstacles, and prospective implementation options. The green economy, by encouraging environmentally friendly practises, resource efficiency, and social inclusion, provides a feasible answer to critical global concerns such as climate change, biodiversity loss, and socioeconomic inequality.